ULTRASONOGRAPHIC DIAGNOSIS OF CYSTIC ENDOMETRIAL HYPERPLASIA-PYOMETRA IN BITCHES - SRIDEVI, P; KULASEKAR, K; ARUNMOZHI, N; RANGASAMY, S; JOSEPH, CECILIA; RAJASUNDARAM, R C (The Indian Journal of Animal Reproduction, 2011)
The use oftransabdominal ultrasonography as a useful and reliable diagnostic method to diagnose Cystic endometrial hyperplasia in bitches is reported.